Genomic features of the Helicobacter pylori strain PMSS1 and its virulence attributes as deduced from its in vivo colonisation patterns. Issue 5 (25th October 2018) - Dyer, Victoria; Brüggemann, Holger; Sörensen, Meike; Kühl, Anja A.; Hoffman, Kirstin; Brinkmann, Volker; Reines, Maria del Mar; Zimmerman, Stephanie; Meyer, Thomas F.; Koch, Manuel
Summary: The human gastric pathogen Helicobacter pylori occurs in two basic variants, either exhibiting a functional cag PAI‐encoded type‐4‐secretion‐system (T4SS) or not. Only a few cag PAI‐positive strains have been successfully adapted for long‐term infection of mice, including the pre‐mouse Sydney strain 1 (PMSS1). Here we confirm that PMSS1 induces gastric inflammation and neutrophil infiltration in mice, progressing to intestinal metaplasia. Complete genome analysis of PMSS1 revealed 1, 423 coding sequences, encompassing the cag PAI gene cluster and, unusually, the location of the cytotoxin‐associated gene A ( cag A) approximately 15 kb downstream of the island. PMSS1 harbours three genetically exchangeable loci that are occupied by the hopQ coding sequences. HopQ represents a critical co‐factor required for the translocation of CagA into the host cell and activation of NF‐κB via the T4SS. Long‐term colonisation of mice led to an impairment of cag PAI functionality. One of the bacterial clones re‐isolated at four months post‐infection revealed a mutation in the cag PAI gene cag W, resulting in a frame shift mutation, which prevented CagA translocation, possibly due to an impairment of T4SS function. Rescue of the mutant cag W re‐established CagA translocation. Our data reveal intriguing insights into the adaptive abilities of PMSS1, suggesting functional modulation of the H. pylori cag PAI virulence attribute. Abstract : PMSS1 is one of very few functional cagPAI+ H. pylori strains capable of colonising the mouse stomach and although it induces high levels of pathogenicity, re‐isolated strains have been reported to lose the ability to translocate CagA. By sequencing the complete genome of PMSS1 we reveal multiple gene loci for the T4SS associated HopQ adhesin and show that a mutation of the cagW gene accounts for secondary loss of the ability to translocate CagA.